Osvrt na kajkavski i štokavske govore Reke kod Koprivnice - Lončarić, Mijo (2018)
U Reki se govori kajkavski i štokavski, i to tri idioma: kajkavski (s dvije starije i jednom novijom varijantom) te dva štokavska. Većina Hrvata govori, odnosno govorila je kajkavski, a manji dio govori istočnobosanskim, ijekavsko-šćakavskim dijalektom. Srbi govore novoštokavskom (i)jekavštinom („novoštakavskom”), istočnohercegovačkim dijalektom. Kajkavski govor, koji je moj rodni idiom, istražio sam za Hrvatski jezični atlas (punkt 37a). Iznosim pretpostavku o jeziku u Podravini prije migracija, govorim o nastanku sela te prikazujem glavne osobine govora. Osvrćem se i na susjedne govore.
People in Reka speak altogether three idioms of Kajkavian and Štokavian: one Kajkavian with three varieties and two Štokavian ones. Most Croats speak, or spoke, Kajkavian, while fewer speak the East-Bosnian Ijekavian-šćakavian dialect. Serbs speak the Neoštokavian Ijekavian („Neoštakavian”, the interrogative pronoun is šta) East-Herzegovinian dialect. I have reviewed the Kajkavian idiom in the monograph Bilogorski kajkavski govori (Kajkavian idioms of Bilogora), and the Štokavian ones in the article Kalničko-bilogorska štokavština (Štokavian idioms of Kalnik and Bilogora). Since the Kajkavian idiom is my native idiom, I undertook a research of it for the Croatian language atlas (point 37a). I make a hypothesis about a language in Podravina before migrations, I speak about how the village emerged and I present the main characteristics of the idioms. I draw parallels with the neighbouring idioms as well.
Bibliografija: str. 328-330.
Sažetak ; Abstract.
Keywords: Hrvatski jezik -- Hrvatska dijalektologija -- Kajkavsko narječje -- Štokavsko narječje; Podravina